Study on the low-velocity impact response and CAI behavior of foam-filled sandwich panels with hybrid facesheet. (15th November 2015) - Yang, Bin; Wang, Zhenqing; Zhou, Limin; Zhang, Jifeng; Tong, Lili; Liang, Wenyan
Abstract: Foam-filled sandwich panels with six types of facesheets were manufactured by vacuum-assisted resin injection (VARI) process. Low velocity impact test and compression after impact (CAI) test of the prepared panels were performed. Failure modes of different sandwich panels were analyzed by observing the contact surface and the cross section through damage region. Scanning electron microscope (SEM) was carried out to study the microstructure of the impacted specimens. It is found that matrix cracking, fiber breaking, foam cracking and debonding are the damage modes of sandwich panel with pure carbon facesheet, while other specimens merely show some of these modes after impact test. Panels with pure carbon facesheet have poor impact resistance properties, while panels with pure glass facesheet have preferable properties among all the specimens. Hybrid panel with ply mode of [C2 /G2 /Foam core/G2 /C2 ] could provide higher maximum contact force and absorb more impact energy by carbon fiber breaking on the contact surface. In CAI test, wrinkling of facesheet and buckling of foam and skin are the two main damage modes. [C4 /Foam core/C4 ] shows highest compress strength decline rate, while [G4 /Foam core/G4 ] shows lowest rate. Decline rate of [C2 /G2 /Foam core/G2 /C2 ] is very low but the compress strength of its undamaged specimen is not high.